Hubungan Interaksi Sosial Dengan Kualitas Hidup Lansia Di Wilayah Kerja Puskesmas Bangkala Kelurahan Biring Romang - Kurniawan Amin; Sigit Mulyono; Lili Herlina (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Quality of life is a level that describes the advantages of an individual that can be assessed from their lives. The purpose of this study was to determine the relationship of social interaction with the quality of life of the elderly in the work area of Bangkala Health Center, Kel. Biring Romang, Kec Manggala, Makassar City. Method: This research is a quantitative study with a type of research with cross-sectional studies with a sample size of 219 respondents using a computerized application of SPSS 20 Che Square test. The results showed that interaction using social media in the elderly P-value = 0,000, which means there is a significant relationship between quality of life in the elderly in the area of Bangkala Health Center, Kel. Biring Romang, Kec. Manggala, Makassar City. Conclusion: There is a relationship between quality of life in the elderly, therefore it is expected that an elderly person should slowly be acquainted with so that in the process of daily life can do social interaction Keywords: Social Interaction, Quality of Life.